Pharmacological Neuroenhancement: Current Aspects of Categorization, Epidemiology, Pharmacology, Drug Development, Ethics, and Future Perspectives - Johanna Daubner; Muhammad Imran Arshaad; Christina Henseler; Jürgen Hescheler; Dan Ehninger; Karl Broich; Oliver Rawashdeh; Anna Papazoglou; Marco Weiergräber (Neural Plasticity)
Recent pharmacoepidemiologic studies suggest that pharmacological neuroenhancement (pNE) and mood enhancement are globally expanding phenomena with distinctly different regional characteristics. Sociocultural and regulatory aspects, as well as health policies, play a central role in addition to medical care and prescription practices. The users mainly display self-involved motivations related to cognitive enhancement, emotional stability, and adaptivity. Natural stimulants, as well as drugs, represent substance abuse groups. The latter comprise purines, methylxanthines, phenylethylamines, modafinil, nootropics, antidepressants but also benzodiazepines, β-adrenoceptor antagonists, and cannabis. Predominant pharmacodynamic target structures of these substances are the noradrenergic/dopaminergic and cholinergic receptor/transporter systems. Further targets comprise adenosine, serotonin, and glutamate receptors. Meta-analyses of randomized-controlled studies in healthy individuals show no or very limited verifiability of positive effects of pNE on attention, vigilance, learning, and memory. Only some members of the substance abuse groups, i.e., phenylethylamines and modafinil, display positive effects on attention and vigilance that are comparable to caffeinated drinks. However, the development of new antidementia drugs will increase the availability and the potential abuse of pNE. Social education, restrictive regulatory measures, and consistent medical prescription practices are essential to restrict the phenomenon of neuroenhancement with its social, medical, and ethical implications. This review provides a comprehensive overview of the highly dynamic field of pharmacological neuroenhancement and elaborates the dramatic challenges for the medical, sociocultural, and ethical fundaments of society.